Importin-β and the small guanosine triphosphatase Ran mediate chromosome loading of the human chromokinesin Kid - Tahara, Kiyoshi (The Rockefeller University Press, 2008)
Nucleocytoplasmic transport factors mediate various cellular processes, including nuclear transport, spindle assembly, and nuclear envelope/pore formation. In this paper, we identify the chromokinesin human kinesin-like DNA binding protein (hKid) as an import cargo of the importin-α/β transport pathway and determine its nuclear localization signals (NLSs). Upon the loss of its functional NLSs, hKid exhibited reduced interactions with the mitotic chromosomes of living cells. In digitonin-permeabilized mitotic cells, hKid was bound only to the spindle and not to the chromosomes themselves. Surprisingly, hKid bound to importin-α/β was efficiently targeted to mitotic chromosomes. The addition of Ran–guanosine diphosphate and an energy source, which generates Ran–guanosine triphosphate (GTP) locally at mitotic chromosomes, enhanced the importin-β–mediated chromosome loading of hKid. Our results indicate that the association of importin-β and -α with hKid triggers the initial targeting of hKid to mitotic chromosomes and that local Ran-GTP–mediated cargo release promotes the accumulation of hKid on chromosomes. Thus, this study demonstrates a novel nucleocytoplasmic transport factor–mediated mechanism for targeting proteins to mitotic chromosomes.